Face-to-face contact during infancy: How the development of gaze to faces feeds into infants’ vocabulary outcomes - Belteki, Zsofia; van den Boomen, Carlijn; Junge, Caroline (Frontiers in Psychology, 2022)
Infants acquire their first words through interactions with social partners. In the first year of life, infants receive a high frequency of visual and auditory input from faces, making faces a potential strong social cue in facilitating word-to-world mappings. In this position paper, we review how and when infant gaze to faces is likely to support their subsequent vocabulary outcomes. We assess the relevance of infant gaze to faces selectively, in three domains: infant gaze to different features within a face (that is, eyes and mouth); then to faces (compared to objects); and finally to more socially relevant types of faces. We argue that infant gaze to faces could scaffold vocabulary construction, but its relevance may be impacted by the developmental level of the infant and the type of task with which they are presented. Gaze to faces proves relevant to vocabulary, as gazes to eyes could inform about the communicative nature of the situation or about the labelled object, while gazes to the mouth could improve word processing, all of which are key cues to highlighting word-to-world pairings. We also discover gaps in the literature regarding how infants’ gazes to faces (versus objects) or to different types of faces relate to vocabulary outcomes. An important direction for future research will be to fill these gaps to better understand the social factors that influence infant vocabulary outcomes.